2016
DOI: 10.1038/srep21183
|View full text |Cite
|
Sign up to set email alerts
|

Post mTBI fatigue is associated with abnormal brain functional connectivity

Abstract: This study set out to investigate the behavioral correlates of changes in resting-state functional connectivity before and after performing a 20 minute continuous psychomotor vigilance task (PVT) for patients with chronic post-concussion syndrome. Ten patients in chronic phase after mild traumatic brain injury (mTBI) with persisting symptoms of fatigue and ten matched healthy controls participated in the study. We assessed the participants’ fatigue levels and conducted resting-state fMRI before and after a sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 51 publications
5
78
0
Order By: Relevance
“…They were not subjects for rehabilitation or any litigation processes, but still when including them in the analyses results were influenced, particularly so the correlation between hormone levels and neuropsychological tests results. In another study on persisting fatigue among self-selected patients with mTBI, we found a reduced connectivity in the thalamus and middle frontal gyrus on fMRI leading to increased activation of cortical networks after a vigilance task [30]. To some extent patients are capable of functional compensation by activating larger brain areas, which also has been proven in patients with thyroid dysfunction [31].…”
Section: Discussionsupporting
confidence: 51%
“…They were not subjects for rehabilitation or any litigation processes, but still when including them in the analyses results were influenced, particularly so the correlation between hormone levels and neuropsychological tests results. In another study on persisting fatigue among self-selected patients with mTBI, we found a reduced connectivity in the thalamus and middle frontal gyrus on fMRI leading to increased activation of cortical networks after a vigilance task [30]. To some extent patients are capable of functional compensation by activating larger brain areas, which also has been proven in patients with thyroid dysfunction [31].…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, subjective fatigue on VAS might not fully reflect fatigue in this study. However, there is no commonly accepted objective measure of fatigue [35]. Furthermore, although fatigue measure was subjective in this study, fatigue scores in the same measure have been reported to correlate with autonomic nervous activity [32,33] and functional connectivity in the brain [35].…”
Section: Discussionmentioning
confidence: 64%
“…However, there is no commonly accepted objective measure of fatigue [35]. Furthermore, although fatigue measure was subjective in this study, fatigue scores in the same measure have been reported to correlate with autonomic nervous activity [32,33] and functional connectivity in the brain [35]. In addition, shift-working nurses with high subjective fatigue on VAS displayed an increase of salivary cortisol level [36].…”
Section: Discussionmentioning
confidence: 64%
“…The age range of all studies was from school level to retirement age (13.5–74 years). Of all included in vivo studies, 22 used an age‐matched control group . All articles were published between 1994 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…From the 25 included studies, 14 used diverse MR techniques . Twenty‐one studies applied structural MRI, including T 1 ‐weighted (T 1 ‐w), T 2 ‐weighted (T 2 ‐w), fluid attenuated inversion recovery (FLAIR), susceptibility weighted imaging (SWI), and proton‐density weighted (PD‐w) imaging . Thirteen studies used diffusion MRI, specifically diffusion tensor imaging (DTI), generalized q‐sampling imaging (GQI), diffusion kurtosis imaging (DKI), and diffusion weighted imaging (DWI) .…”
Section: Resultsmentioning
confidence: 99%